An unusual coalition of medullary nephrocalcinosis with a novel genotypic variant of Alport syndrome type-1 - Pradhan, Poonam; Kapat, Aritra; Mandal, Asok K.; Bala, Ashok K. (International Journal of Research in Medical Sciences, 2023)
Alport’s syndrome is a type of inherited disorder of the basement membrane characterized by a spectrum of phenotypes ranging from progressive renal injury to varied extrarenal manifestations comprising auditory and ocular abnormalities. Here in, we present a 3-year-old child born out of nonconsanguineous marriage who presented with fever, intermittent microscopic haematuria, and recurrent gross haematuria, proteinuria with normal auditory brainstem response and ocular slit lamp examination findings. Renal biopsy yielded normal light microscopy and immunofluorescence study whereas minimal changes in the glomerular basement membrane (GBM) collagen were detected on electron microscopy, suggesting possibilities of Alport’s syndrome. Ultrasonographic renal imaging yielded the presence of bilateral medullary nephrocalcinosis. Angiotensin converting enzyme inhibitors along with angiotensin receptor blockers were used to curb the disease progression. A final clinical exome sequencing corroborated the phenotype with a diagnosis of Alport’s syndrome type-1 linked to a novel pathogenic variant c.1892dup (p.Gly632ArgfsTer2) showing hemizygous single base pair insertion/duplication in COL4A5 gene. To the best of our knowledge, this unusual association of Alport’s syndrome with medullary nephrocalcinosis has not been reported worldwide in any previous medical literature making this report a primi one.